Design and Synthesis of Brefeldin A-Isothiocyanate Derivatives with Selectivity and Their Potential for Cervical Cancer Therapy - Mingying Wang; Xiaoyuan Chen; Ying Qu; Qingyinglu Ma; Huaqi Pan; Haonan Li; Huiming Hua; Dahong Li (Molecules, 2023)
Brefeldin A has a wide range of anticancer activity against a variety of tumor cells. Its poor pharmacokinetic properties and significant toxicity seriously hinder its further development. In this manuscript, 25 brefeldin A-isothiocyanate derivatives were designed and synthesized. Most derivatives showed good selectivity between HeLa cells and L-02 cells. In particular, 6 exhibited potent antiproliferative activity against HeLa cells (IC50 = 1.84 μM) with no obvious cytotoxic activity to L-02 (IC50 > 80 μM). Further cellular mechanism tests indicated that 6 induced HeLa cell cycle arrest at G1 phase. Cell nucleus fragmentation and decreased mitochondrial membrane potential suggested 6 could induce apoptosis in HeLa cells through the mitochondrial-dependent pathway.